Understanding the Effect of Generation through the Sustainability of OMNI-channel Commerce - Issarin Kulchitaphong; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (My University, 2021)
Popularity from each generation effects the economic movement, especially the retail business, which expected to have a slight decrease at 5-8% due to the customer's behavior, ideas, and lifestyle that change with the era. This research aims to build a conceptual framework based on IS success model and loyalty model for initially studying the strategy model of OMNI business sustainability with intensely focusing on generation factors and understanding the attitude of each generation. This research would a better understand potential factors affecting the model of OMNI business sustainability on generations. Then, for further research after data collection, the AMOS program will be used to analyze the relationship of variables to develop sustainable practices in OMNI businesses from the perspective of consumers of each generation such as Baby Boom, X, Y, and Z.
Keywords: Technology Adoption and User Behaviour; Digital Marketing and Social Media; Consumer Retail Behavior Studies